EVALUATION OF SCAFFOLDS IN VITRO FOR USE IN TENDON REGENERATION. Issue 9 (10th May 2013) - Cornish, J; Musson, D S
Abstract : Introduction: Injuries to tendons can cause major morbidity in healthy, young active people as well as in the increasing aged population. Providing a scaffold that encourages appropriate cell attachment, growth, and ultimately tissue regeneration, could improve the clinical outcomes from injuries such as rotator cuff tears. Millions of dollars are spent annually on the development of biomaterial scaffolds and many are put into clinical use without proper cell compatibility and immunogenicity evaluation leading to many instances of unfavourable results with associate patient morbidity. The purpose of this study was to set-up an evaluation package to assess scaffold materials of both natural and synthetic origin for their potential utility in tendon regenerative medicine. Methods: Two novel scaffolds were evaluated as biomaterials: Spidrex 543 (Oxford Biomaterials Ltd, UK), a spider-like silk fabric; and Endoform (Mesynthes, New Zealand), a decellularised ovine forestomach matrix then compared to three-dimensional (3D) collagen gels as a control and FiberWire (Athrex. Inc, USA), a polyethylene and polyester composite suture, which is currently utilised in orthopaedic surgery. Primary human dendrocytic cells were exposed to scaffolds, with cell-surface activation markers analysed using FACS to determine scaffold immunogenicity. Attachment and growth of primary tenocytes were analysed using live-dead staining and alamar Blue fluorescence. Phenotypic retention was assessed through morphological studies, while real-time PCR was employed to evaluate cell differentiation. Results: FACS analysis determined that Spidrex 543, invoked a high immune response in the primary human dendrocytes, while Endoform and the 3D collagen gels provided relatively low immunogenicity. FiberWire, the synthetic suture material currently used in orthopaedic surgery produced relatively high immune activation within these cells. Tenocytes successfully adhered to and grew on the Endoform, Spidrex 543 and within the 3D collagen gels, whereas the orthopaedic suture material proved unsuitable for cell attachment/growth. Gene analysis and morphology in the three permissible scaffolds suggest cells retain their phenotype when cultured in them. Discussion: 3D culture systems support and amplify tenocyte proliferation and differentiation whilst gene expression data indicated increases of tenocyte-like markers, such as tenomodulin, scleraxis and collagen IA1 We have developed an in vitro evaluation package to identify the biocompatibility of biomaterial scaffolds- whether the materials support and promote target cell growth and have potential for use in tendon regeneration. Much time and expense can be saved by such in vitro evaluation of biomaterials prior to embarking on in vivo studies.